2012
DOI: 10.1111/j.1748-0361.2012.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity Among Adults From Rural and Urban Areas of the United States: Findings From NHANES (2005‐2008)

Abstract: Purpose Rural residents have higher rates of chronic diseases compared to their urban counterparts, and obesity may be a major contributor to this disparity. This study is the first analysis of obesity prevalence in rural and urban adults using body mass index classification with measured height and weight. In addition, demographic, diet, and physical activity correlates of obesity across rural and urban residence are examined. Methods Analysis of body mass index (BMI), diet, and physical activity from 7,325… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
450
10
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 493 publications
(489 citation statements)
references
References 23 publications
25
450
10
4
Order By: Relevance
“…Still, some studies show that rural residents may experience decreased life expectancy and increased all-cause and disease-specific mortality, particularly with respect to some cancers, compared to urban residents (Singh and Siahpush 2014a, b;LeVault et al 2014;Colli et al 2009;Cole et al 2012;Colleran et al 2007;Singh 2012;Fogleman et al 2015). Some incidence and mortality differences may be attributed to the increased prevalence of smoking, obesity, and alcohol use in many rural areas (Befort et al 2012;Doescher et al 2006;Jackson et al 2005Jackson et al , 2006. Alternatively, the history and geography of many rural American communities are suitable for an underlying genetic heterogeneity in disease susceptibility to arise due to possible founder effects and relative geographic isolation (Jenkins et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Still, some studies show that rural residents may experience decreased life expectancy and increased all-cause and disease-specific mortality, particularly with respect to some cancers, compared to urban residents (Singh and Siahpush 2014a, b;LeVault et al 2014;Colli et al 2009;Cole et al 2012;Colleran et al 2007;Singh 2012;Fogleman et al 2015). Some incidence and mortality differences may be attributed to the increased prevalence of smoking, obesity, and alcohol use in many rural areas (Befort et al 2012;Doescher et al 2006;Jackson et al 2005Jackson et al , 2006. Alternatively, the history and geography of many rural American communities are suitable for an underlying genetic heterogeneity in disease susceptibility to arise due to possible founder effects and relative geographic isolation (Jenkins et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, geographic disparity exists in weight status, with national estimates for obesity being higher in rural regions of the USA compared with urban areas (2,3) . Data from the 2005-2008 National Health and Nutrition Examination Survey indicated that the obesity prevalence in rural areas was 39·6 % compared with 33·4 % in urban areas (3) . Dietary intake remains an important focus in the prevention of overweight and obesity.…”
Section: African American Validity Fat Intake Fruit and Vegetable Intakementioning
confidence: 99%
“…Indeed, the obesity prevalence rate was 39.6 percent of rural adults compared to 33.4 percent of urban adults, and remained significantly higher even after controlling for demographic, diet, and physical activity (Befort, Nazir, & Perri, 2012). Even for children, living in rural versus metropolitan areas was associated with being overweight or obese (Lutfiyya, Lipsky, Wisdom-Behounek, & Inpanbutr-Martinkus, 2007).…”
Section: Introductionmentioning
confidence: 97%